STRUKTUR ANATOMI BEBERAPA JENIS KAYU HUTAN TANAMAN INDUSTRI - Sri Rulliaty M; Y I Mandang (Jurnal Penelitian Hasil Hutan, 1988)
Gross and  anatomical  features  of  nine Industrial  Forest  Plantation Timber  Species  were studied  and described  for identification  purposes. The  result  shows  that  each wood  species   can be  distinguished one  from  the other  except those species  which  belong  to  the same genera.